Patterns of Biomass and Carbon Allocation across Chronosequence of Chir Pine (Pinus roxburghii) Forest in Pakistan: Inventory-Based Estimate - Muhammad Amir; Xiaodong Liu; Adnan Ahmad; Sajjad Saeed; Abdul Mannan; Muhammad Atif Muneer (Advances in Meteorology)
The quantitative relationship between carbon sequestration potential and stand ages of Pine (Pinus roxburghii) forest is not documented in Pakistan. Using field inventory data, this study underlines the patterns of biomass and carbon allocation across a chronosequence of Chir Pine forest. Based on the uniform shelterwood silvicultural management system, the forest was classified into three stand age classes representing the young stand (<50 years), mature stand (50–75 years), and overmature stand (> 75 years). The results showed an increasing trend in living tree biomass carbon with stand age. However, soil carbon showed gradually decreasing trend from young to overmature stand. Similarly, deadwood, litter, and understory biomass carbon showed an increase pattern of changes. Altogether, the results highlighted that the mean carbon values of all components varied between 90.3 t·C·ha−1 in the young stand and 309.5 t·C·ha−1 in the overmature stand. Furthermore, our results confirm that the current management operations affect the forest floor and soil carbon. Therefore, we suggest that different protection measures should be considered during management operations to enhance soil and forest floor carbon.